Implementation of Deep Breathing Relaxation, Distraction Techniques, Therapeutic Communication, and Spiritual Therapy to Prevent Violent Behavior in Patients with Schizophrenia - Nabila, Nisrina; Rismawan, Wawan (FORIKES, 2026)
One of the most commonly encountered and treated mental disorders is schizophrenia, which is characterized by disturbances in reality testing, cognitive functioning, and difficulties in performing daily activities. Patients with schizophrenia tend to be at high risk of engaging in violent behavior. This study aimed to describe nursing care interventions, particularly deep-breathing relaxation, distraction techniques, therapeutic communication, and spiritual therapy, in preventing violent behavior among patients with schizophrenia. This study employed a case report method involving four patients with the primary nursing diagnosis of risk for violent behavior. Nursing care was subsequently implemented, and the outcomes were presented descriptively. The results showed that nursing therapeutic interventions enabled patients to control emotions and violent behavior through deep-breathing relaxation; patients were able to perform emotional distraction by hitting a pillow, communicate appropriately, adhere to medication regimens, and engage in spiritual activities, thereby preventing violent behavior. Nursing therapy was conducted over seven days with the implementation of SP I–V. It can be concluded that the deep-breathing relaxation technique helps patients with schizophrenia control violent behavior. Psychiatric nurses are therefore recommended to apply this technique comprehensively for patients exhibiting violent behavior.Keywords: schizophrenia; risk of violent behavior; psychiatric nursing care; deep-breathing relaxation